Bacterial and fungal communities within and among geographic samples of the hemp pest Psylliodes attenuata from China - Guo, Litao; Tang, Chao; Gao, Chunsheng; Li, Zhimin; Cheng, Yi; Chen, Jia; Wang, Tuhong; Xu, Jianping (Frontiers in Microbiology, 2022)
The hemp flea beetle Psylliodes attenuata (Coleoptera: Chrysomelidae: Psylliodes) is a common pest of Cannabis sativa, including cultivars of both medicinal marijuana and industrial hemp. Both the larval and adult stages of this beetle can cause significant damages to C. sativa, resulting in substantial crop losses. At present, little is known about the bacterial and fungal community diversity among populations of this pest insect. In the present study, we obtained P. attenuata samples from nine field sites representing broad industrial hemp productions in China and analyzed their microbial communities using DNA metabarcoding. Bacterial sequences of all the samples were assigned to 3728 OTUs, which belonged to 45 phyla, 1058 genera and 1960 known species. The most common genera were Rickettsia, Wolbachia and Candidatus_Brownia. Fungal sequences of all the samples were assigned to 910 OTUs, which belonged to 9 phyla, 308 genera and 464 known species. The most common fungal genera were Cladosporium, Cutaneotrichosporon and Aspergillus. Principal coordinate analysis revealed a significant difference in the bacterial and fungal community structure among the nine P. attenuata populations. Understanding the microbial symbionts may provide clues to help develop potential biocontrol techniques against this pest.